Self-Hybridized Exciton-Polaritons in Sub-10-nm-Thick WS2 Flakes: Roles of Optical Phase Shifts at WS2/Au Interfaces - Anh Thi Nguyen; Soyeong Kwon; Jungeun Song; Eunseo Cho; Hyohyeon Kim; Dong-Wook Kim (Nanomaterials, 2022)
Exciton–polaritons (EPs) can be formed in transition metal dichalcogenide (TMD) multilayers sustaining optical resonance modes without any external cavity. The self-hybridized EP modes are expected to depend on the TMD thickness, which directly determines the resonance wavelength. Exfoliated WS2 flakes were prepared on SiO2/Si substrates and template-stripped ultraflat Au layers, and the thickness dependence of their EP modes was compared. For WS2 flakes on SiO2/Si, the minimum flake thickness to exhibit exciton–photon anticrossing was larger than 40 nm. However, for WS2 flakes on Au, EP mode splitting appeared in flakes thinner than 10 nm. Analytical and numerical calculations were performed to explain the distinct thickness-dependence. The phase shifts of light at the WS2/Au interface, originating from the complex Fresnel coefficients, were as large as π/2 at visible wavelengths. Such exceptionally large phase shifts allowed the optical resonance and resulting EP modes in the sub-10-nm-thick WS2 flakes. This work helps us to propose novel optoelectronic devices based on the intriguing exciton physics of TMDs.